COASTAL ENVIRONMENTAL DEGRADATION IN KUPANG CITY (2018–2024): A SYSTEMATIC REVIEW AND POLICY IMPLICATIONS FOR CONSERVATION - Nuban, Sri Rahayu; Lukmini, Aisyah; Yosefa Salu, Susanti Maria (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2025)
This study conducts a systematic literature review to examine coastal environmental degradation in Kupang City between 2018 and 2024, focusing on shoreline erosion, mangrove deforestation, sedimentation, water quality decline, and biodiversity loss. The objective is to evaluate the extent of degradation and analyze how current conservation policies align with scientific findings. Using the PRISMA 2020 framework, the review incorporates 25 peer-reviewed articles and official reports published between 2018 and 2024. The analysis highlights that major degradation indicators are concentrated in highly developed coastal zones such as Bolok, Lasiana, and Oesapa. Geospatial assessments using the Digital Shoreline Analysis System (DSAS), NDVI, and Total Suspended Solids (TSS) revealed substantial shoreline retreat, mangrove loss exceeding 35%, and seasonal spikes in turbidity levels. Despite the availability of national and regional conservation frameworks, their implementation remains fragmented due to weak coordination, lack of adaptive planning, and limited use of scientific data. Community-based conservation efforts have demonstrated localized success but remain outside formal policy mechanisms. The study proposes an adaptive governance framework that integrates big data, remote sensing, socio-economic mapping, and participatory planning to strengthen resilience. Additionally, it suggests leveraging blue economy strategies, enhancing institutional capacity, and embedding conservation into economic policy as pathways toward sustainable coastal management. This research contributes an evidence-based model for improving conservation outcomes in Kupang and similar urban coastal settings across Indonesia.